LI-RADS-CEUS - Proposal for a Contrast-Enhanced Ultrasound Algorithm for the Diagnosis of Hepatocellular Carcinoma in High-Risk Populations - Schellhaas, B.; Wildner, Dane; Pfeifer, Lukas; Görtz, Rüdiger; Hagel, Alexander; Neurath, Markus; Strobel, Deike (Ultraschall in der Medizin, 2016)
Purpose: To develop a contrast-enhanced ultrasound algorithm (LI-RADS-CEUS = liver imaging reporting and data system with contrast-enhanced ultrasound) for the diagnosis of hepatocellular carcinoma (HCC) in patients at risk. Materials and Methods: A CEUS algorithm (LI-RADS-CEUS) was designed analogously to CT- and MRI-based LI-RADS. LI-RADS-CEUS was evaluated retrospectively in 50 patients at risk with confirmed HCC or non-HCC lesions (test group) with subsequent validation in a prospective cohort of 50 patients (validation group). Results were compared to histology, CE-CT and CE-MRI as reference standards. Results: Tumor diagnosis in the test group/validation group (n = 50/50) were 46/41 HCCs, 3/3 intrahepatic cholangiocellular carcinomas (ICCs) and 1/6 benign lesions. The diagnostic accuracy of LI-RADS-CEUS for HCC, ICC and non-HCC-non-ICC-lesions was 89 %. For the diagnosis of HCC, the diagnostic accuracy was 93.5 % (43/46 cases) in the test group and 95.1 % (39/41 cases) in the validation group. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 94.3 %, 66.6 %, 94.3 % and 66.6 %, respectively (mean values from both cohorts). Histological findings of HCC were available in 40 versus 23 cases (in total: G1 / G2/G3: 15/35/13). Arterial hyperenhancement was seen in 68/87 (78.2 %) of HCCs. Arterial hyperenhancement with subsequent portal venous or late phase hypoenhancement was seen in 66 % of HCCs. Conclusion: LI-RADS-CEUS offers a CEUS algorithm for standardized assessment and reporting of focal liver lesions in patients at risk for HCC. Arterial hyperenhancement in CEUS is the key feature for the diagnosis of HCC in patients at risk, whereas washout is not a necessary prerequisite.
EVALuna2:2223